A new Puccini a on endemic Phryna - Hüseyin, Elşad; Kirba?, Sevda (My University, 2003)
The rust fungus Puccinia phrynae sp. nov. is described and illustrated from endemic Phryna ortegioides collected in East Anatolia, Turkey.